Analysis of Changes In Biofloc Wastewater Quality Following Eco-Enzyme Application - Nor Inayah; Noor Arida Fauzana; Fatmawati; Pahmi Ansyari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The biofloc system improves water- and feed-use efficiency but generates wastewater containing suspended solids and nitrogenous compounds that require treatment before reuse. This study evaluated changes in biofloc wastewater quality after the addition of eco-enzyme at concentrations of 0% (control), 5%, 10%, 15%, 20%, and 25% (v/v). The wastewater and eco-enzyme were homogenized, incubated for 24 h, and analyzed for pH, dissolved oxygen (DO), ammonia (NH₃), total suspended solids (TSS), total nitrogen, total phosphorus, total potassium, and the C/N ratio. Data from two measurement replicates were analyzed using one-way analysis of variance followed by Fisher's least significant difference (LSD) test at the 5% significance level. Eco-enzyme had a highly significant effect on pH (p < 0.001), a significant effect on DO (p = 0.012), and a highly significant effect on NH₃ (p < 0.001). The pH increased from 2.760 in the control to 3.145 at the 25% dose, whereas DO decreased from 2.650 to 2.500 mg/L and NH₃ increased from 0.500 to 2.000 mg/L. TSS, total nitrogen, and total phosphorus did not differ significantly among treatments (p > 0.05). Total potassium increased from 0.0015% to 0.0705% (p < 0.001), while the C/N ratio increased from 0.460 to 6.310 (p = 0.004). These findings indicate that, after 24 h of contact, eco-enzyme functions more as a carbon source and a mineralization bioactivator than as a stand-alone treatment capable of directly producing water suitable for aquaculture. The treated water still requires neutralization, aeration, ammonia control, and a longer maturation period before reuse.